The path to below replacement fertility in the Islamic Republic of Iran - Mohammad Jalal Abbasi-Shavazi; Meimanat Hosseini-Chavoshi; Peter McDonald (Asia-Pacific Population Journal, 2007)
Low fertility has become an important area of demographic research as fertility in many countries has fallen to levels well below replacement. Advanced countries have experienced low fertility trends for decades (United Nations, 2000), and some are experiencing lowest-low fertility (i.e. TFR below 1.3) (Kohler, Billari and Ortega, 2002; Caldwell, 2006). Less developed countries, by contrast, have recently experienced low fertility levels, and there no longer seem to be any barriers to most countries reaching replacement level and subsequently falling below that level. According to the United Nations, by 2000, around 44 per cent of the world population lived in countries where fertility had fallen below the replacement level. This proportion is expected to increase to 67 per cent by the year 2015 (United Nations, 2000). According to the United Nations median variant projections, approximately 80 per cent of the world’s population is projected to live in countries with below-replacement fertility before mid-century (United Nations, 2002a). Several East and North-East, as well as North and Central Asian countries have attained below replacement in recent decades (Gubhaju and Moriki-Durand, 2003; Atoh, 2001; Hirschman, Chamratrithirong and Guest, 1994; Knodel, Chamratrithirong and Debavalya, 1987). However, countries have attained low fertility in different ways (Perelli-Harris, 2005) and thus, every country and region may have a unique experience in reaching low fertility. For instance, Hirschman, Chamratrithirong and Guest (1994) have argued that the distinctive attributes of East Asian countries such as Hong Kong, China; Singapore; the Republic of Korea; and Taiwan Province of China in terms of rapid economic growth and Confucian cultural heritage would not make them a model for fertility decline in other countries in Asia.